Knock, knock! who׳s there? Putting the user in control of managing interruptions. Issue 79 (July 2015) - Grandhi, Sukeshini A.; Jones, Quentin
Abstract: The abundance of communication technology, such as the omnipresence of cell phones, has not only increased our ability to reach people anytime anywhere, but also the likelihood of being interrupted. As a result, there is value in understanding how to design technology so that gains are realized from desired interruptions, while the losses from unwanted interruptions are minimized. This paper presents the findings of two complementary field studies, one quantitative and the other qualitative, exploring how the provision of additional incoming cell phone call information impacts people׳s interruption decision making. These studies were enabled by, Telling Calls, a research application built to enable users to provide and receive information such as what the call is about and the caller׳s circumstances. The qualitative study showed how the additional call information helps people make informed call handling decisions and acts as an aid to effective conversation. The quantitative study elucidated these findings and showed that reducing the uncertainty about the nature of an incoming call improves people׳s ability to predict the value of an interruption. By combining these diverse research approaches: (1) theory instantiation through tool building; (2) context-aware surveys; and (3) semi-structured interviews, we were able to gain unique insights into the nature of interruption management in the wild, and related design implications. Highlights: Presents 2 field studies of people׳s interruption handling behavior in cell phones. Explores the value of providing additional caller and call related information. Having additional information enables informed call handling decisions. Provides implications for design of interpersonal interruption management tools.